Pelatihan Kepemimpinan Ibadah Bagi Siswa-Siswi Kristen SMA: Mempersiapkan Generasi Pelayan yang Siap dan Beriman - Roy Stevanus; Ribka Siwalette (Lembaga Pengembangan Kinerja Dosen, 2025)
Worship leadership training represents a strategic initiative in nurturing the spiritual character of Christian students from their adolescent years. This program was implemented at SMA Hidup Baru Ciumbeluit in March 2023, with the primary objective of equipping students to lead worship services independently and responsibly. The training employed a hands-on, experiential approach, granting students the opportunity to design and lead complete worship sessions. The outcomes demonstrated notable improvements in self-confidence, coordination skills, and the students’ comprehension of Christian liturgical structure. Furthermore, the program served as a platform for character formation, instilling values such as discipline, collaboration, and servant-oriented leadership. This article explores the theological, educational, and psychological dimensions of student involvement in worship leadership. The initiative proved to be an effective model for preparing the younger generation to actively engage in ministry, both within the school environment and in broader ecclesial and community contexts. As such, similar training programs are recommended to be conducted regularly as an integral part of faith development and discipleship for Christian youth.